An integrated robust iterative learning control strategy for batch processes based on 2D system. (January 2020) - Zhou, Liuming; Jia, Li; Wang, Yu-Long; Peng, Daogang; Tan, Wendan
Highlights: Considering the problems of constraints, nonlinearity and parameter uncertainties, we add a robust iterative learning controller into 2D system. Then integrated control methods are proposed. The analyses of robust convergence and tracking performance based on 2D system are given in this paper. The proposed control strategy can effectively improve the robustness of the system. Abstract: This paper studies the problem of integrated control in the 2-dimensional (2D) system with parameter uncertainties for batch processes. An integrated iterative learning control (ILC) strategy based on quadratic performance for batch processes is proposed. It realizes comprehensive control by combining robust ILC in batch-axis with model predictive control (MPC) in time-axis. The design of quadratic-criterion-based ILC for the system can be converted into a min-max problem. Then a model predictive controller with time-varying prediction horizon is designed based on a quadratic cost function. For an uncertain model, a novel integrated robust ILC scheme based on a nominal model is further proposed. As a result, the control law of the 2D system can be regulated during one batch, which leads to good tracking performance and strong robustness against the disturbance and the uncertainties. Moreover, the analyses of the convergence and tracking performance are given. The proposed methods are applied to batch reactor, and results demonstrate that the system has good robustness and convergence. This paper provides a new way for batch processes control.